Synthesis, characterization and spectroscopic studies on Schiff base complexes of 1-phenyl-2, 3-dimethyl-4-amino-5-oxo-pyrazole with salicylaldehyde with some divalent transition metals (Baghdad Science Journal, 2011)
In this research, the preparation of bidentate Schiff base was carried out via the condensation reaction of both the salicylaldehyde with 1-phenyl-2,3-dimethyl-4-amino-5-oxo-pyrazole to form the ligand (L). The mentioned ligand was used to prepare complexes with transition metal ions Mn(II), Co(II), Ni(II), Cu(II) and Zn(II). The resulting complexes were separated and characterized by FTIR and UV-Vis spectroscopic technique. Elemental analysis for Carbon, Hydrogen and Nitrogen elements, electronic spectra of the ligand and complexes were obtained, and the magnetic susceptibility tests were also achieved to measure the dipole moments. The molar conductivities were also measured and determination of chlorine content in the complexes and the metal ratio. The complexes have shown the octahydral shapes in the general formula [ML2Cl2], whereas M=Mn, Co, Ni, Cu and Zn, ligand which coordinated as bidentate behavior with nitrogen and oxygen as donor atoms.